2020
DOI: 10.1016/j.pmedr.2020.101223
|View full text |Cite
|
Sign up to set email alerts
|

The health belief model and colorectal cancer screening in the general population: A systematic review

Abstract: Colorectal cancer screening saves lives and is cost-effective. It allows early detection of the pathology, and enables earlier medical intervention. Despite clinical practice guidelines promoting screening for average risk individuals, uptake remains suboptimal in many populations. Few studies have examined how sociobehavioural factors influence screening uptake in the context of behaviour change theories such as the health belief model. This systematic review therefore examines how the health belief model’s c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 61 publications
6
72
0
8
Order By: Relevance
“…The shortest disease course of patients in this study was 6 months and the longest was 12 years; 82.8% of patients had other chronic diseases such as diabetes, hypertension, [8], and 6.1% [10] of patients, respectively.…”
Section: Disease-related Informationmentioning
confidence: 59%
See 2 more Smart Citations
“…The shortest disease course of patients in this study was 6 months and the longest was 12 years; 82.8% of patients had other chronic diseases such as diabetes, hypertension, [8], and 6.1% [10] of patients, respectively.…”
Section: Disease-related Informationmentioning
confidence: 59%
“…The purpose of this study is to investigate the current status of exercise participation in patients after radical gastric cancer surgery based on the knowledge-attitudepractice pattern (8), and analyze its influencing factors, so as to provide guidance and reference for the targeted improvement of patients' exercise participation levels after radical gastric cancer surgery.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The Health Belief Model (HBM) [24] as applied to cancer prevention was used to guide the intervention and data analysis (Figure 1). The HBM has been widely used to measure the health beliefs and behaviors about cancer screening [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Another study by Huang et al [ 30 ] suggested that variables pertinent to the TPB could successfully predict colorectal cancer screening uptake. Further, the HBM was effective to improve colorectal cancer screening uptake in general [ 31 ]. Cervical cancer screening, on the other hand, was predicted by using the TPB [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%